KAJIAN POTENSI WISATA MINAT KHUSUS DI KAMPUNG WAE REBO KABUPATEN MANGGARAI PROVINSI NUSA TENGGARA TIMUR - , Handrianus Gampung ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Wae Rebo village is located in Satar Lenda, Manggaraian regency, NTT, yet nowadays has develop to be one of the tourism destination. It occurs since the locals attempt to maintain their traditional houses called mbaru niang. The aim of the research are a) to describe the tourism potency in Wae Rebo village whether it has been developed or not. And, b) to explain the local perspective about those activities and how their acceptance toward the existence of the visitors. The research applied qualitative method wherein construct an observation to research objects such as attractive tourism opportunities in Wae Rebo village, and making an interview to obtain much of information about the form of tourism activities and local opinion about tourism in the area, therefore the research process can be illustrated descriptively. The research shows that the special interest tourism activities in Wae Rebo village have significantly increased, with mbaru niang as the main object. Nonetheless, there are also many tourism objects such as natural tourism objects, plants and animals, and traditional culture, which have opportunity to be developed as tourism attractions to gain more visitors. These tourism objects will create much more tourism activities such as to know and to learn the structure of mbaru niang as traditional house, to enjoy arts, customs and culture exhibition, tracking, and ecotourism activities. Subsequently, the changing process of Wae Rebo village to become one of the tourism destinations which attract many visitors meets the localâs understanding. It occurs when the existence of the foreign visitors have influence the local to protect and to preserve their cultures and customs. Tourism is well developing in Wae Rebo village, so the locals will gain positive impact by applying a good development system. Therefore, it needs consequently lots of attentions from the government to contiguous and to increase either natural or human resources especially Wae Rebo villagers so the development process will meet its goal and maintain the sustainability.